Effects of high-intensity interval training on health-related quality of life in chronic lymphocytic leukemia: A pilot study. Issue 1 (January 2023) - Artese, Ashley L.; Sitlinger, Andrea; MacDonald, Grace; Deal, Michael A.; Hanson, Erik D.; Pieper, Carl F.; Weinberg, J. Brice; Brander, Danielle M.; Bartlett, David B.
Abstract: Introduction: Chronic lymphocytic leukemia (CLL) is the most common incurable leukemia/lymphoma in the United States. Individuals with CLL are at risk for disability, frailty, and cancer-specific complications that negatively affect health-related quality of life (HRQOL). High-intensity interval training (HIIT) and resistance training (RT) are safe and feasible for individuals with chronic diseases and when combined, they may be beneficial for reducing cancer-related fatigue, symptom burden, and global quality of life. However, no studies have examined the impact of HIIT or RT on HRQOL in CLL. The purpose of this study was to investigate the effects of a 12-week HIIT and RT (HIIT+RT) intervention on HRQOL in adults with treatment naïve CLL. Materials and Methods: Changes in HRQOL was a secondary outcome in this pilot study. Individuals with CLL (63.9 ± 8.5 yrs) were non-randomly assigned to 12 weeks of HIIT+RT or a control group. The HIIT+RT protocol consisted of three 30-min sessions/week of HIIT and two sessions/week of RT. The control group maintained usual daily activities. We assessed pre and post HRQOL using the Functional Assessment of Cancer Therapy-Lymphoma (FACT-Lym) questionnaire with domains of physical (PWB), social (SWB), emotional (EWB), functional (FWB), and general (FACT-G) well-being as well as a lymphoma-specific subscale (LymS). We used a two-way mixed analysis of variance to assess changes in HRQOL. We calculated effect size (ES) using Cohen's d . Results: Fifteen participants (HIIT+RT: n = 9; Control: n = 6) completed the study and questionnaire. Scores for FWB improved following HIIT+RT (21.7 ± 3.4 to 23.9 ± 3.2; ES = 1.38) compared to controls (25.7 ± 2.2 to 25.7 ± 2.3). The HIIT+RT group experienced clinically meaningful improvements in total FACT-Lym, FWB, FACT-G, and LymS. The control group had clinically meaningful changes only in LymS. Discussion: The large effect sizes and clinically meaningful improvements associated with 12 weeks of HIIT+RT support the potential benefits of this type of exercise program for FWB, lymphoma-specific symptoms, and general well-being in CLL. A future randomized trial with an adequately powered sample size is needed to evaluate these findings. Trial Registration: NCT04950452